Potential solution in sustainable agriculture: improving the pH and pH buffering capacity of gray soil Acrisol from Cu Chi, Ho Chi Minh City, Vietnam using biochar combined with bentonite - Hoang, Nguyen Khanh; Phuong, Nguyen Van; Long, Le Ba (Universitas Sebelas Maret, 2023)
The acidification of agricultural soils should be avoided, and low pH soils should be corrected for better productivity. Soil improvement by applying biochar from agricultural byproducts combined with bentonite, a rich source in Vietnam, is a trend in green agriculture in the country. The current study is important in assessing the potential influences of biochar and bentonite on the pH and pH buffering capacity (pHBC) of low pH soil collected in Cu Chi, Ho Chi Minh City, Vietnam. Experimental methods, including biochar preparation (pyrolysis at 300°C, retention time: 2 h), soil incubation (time: 30 days, temperature: 27°C), and pH and pHBC determination, were performed. Research results have shown that biochar and bentonite have contributed to improving the pH and pHBC of gray soil samples. Using 1% bentonite and 1% biochar raised the pH to 6.21 and improved the pHBC of Cu Chi gray soil to 24.1 mmolH+/OH- kg-1. This dose is currently suitable for agricultural production in Vietnam. The study confirmed the applicability of biochar derived from cow manure prepared at a low pyrolysis temperature in combination with bentonite to improve soil parameters such as pH and pHBC in Cu Chi gray soil.